A pulse‐chase strategy combining click‐EdU and photoconvertible fluorescent reporter: tracking Golgi protein dynamics during the cell cycle. Issue 2 (30th September 2014) - Bourge, Mickaël; Fort, Cécile; Soler, Marie‐Noëlle; Satiat‐Jeunemaître, Béatrice; Brown, Spencer C.
Summary: Imaging or quantifying protein synthesis in cellulo through a well‐resolved analysis of the cell cycle (also defining G1 subcompartments) is a methodological challenge. Click chemistry is the method of choice to reveal the thymidine analogue 5‐ethynyl‐2′‐deoxyuridine (EdU) and track proliferating nuclei undergoing DNA synthesis. However, the click reaction quenches fluorescent proteins. Our challenge was to reconcile these two tools. A robust protocol based on a high‐resolution cytometric cell cycle analysis in tobacco ( Nicotiana tabacum ) BY2 cells expressing fluorescent Golgi markers has been established. This was broadly applicable to tissues, cell clusters, and other eukaryotic material, and compatible with Sca l e clearing. EdU was then used with the photoconvertible protein sialyl transferase (ST)‐Kaede as a Golgi marker in a photoconversion pulse‐chase cytometric configuration resolving, in addition, subcompartments of G1. Quantitative restoration of protein fluorescence was achieved by introducing acidic EDTA washes to strip the copper from these proteins which were then imaged at neutral pH. The rate of synthesis of this Golgi membrane marker was low during early G1, but in the second half of G1 (30% of cycle duration) much of the synthesis occurred. Marker synthesis then persisted during S and G2. These insights into Golgi biology are discussed in terms of the cell's ability to adapt exocytosis to cell growth needs.